Analisis Kelayakan Usaha Bengkel Sepeda Motor di Kecamatan Wonocolo Kota Surabaya - Muhammad Rois Afdlol; Arga Christian Sitohang (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
This research aims to analyze the feasibility level of a motorbike repair shop business in Wonocolo subdistrict, Surabaya city. This research data analysis uses the method of calculating fixed costs, variable costs, total costs, revenues, income and business feasibility. In this research, the analysis used is B/C, R/C and ROI. The results of the research show that the average total cost for 6 informants who own a motorbike repair shop is IDR38,971,456/month, the revenue obtained is an average of IDR100,575,500/month and the average income is IDR 61,604,043/month. Calculation of business feasibility using the b/c ratio obtained an average result of 1.60%, the average r/c ratio calculation was 2.60% and the average ROI calculation was 118.667%. The results of these calculations state that the motorbike repair shop business in Wonocolo subdistrict, Surabaya city is feasible to run and develop.